Physical Education and quality of life: reflections and perspectives - Santos, Ana Lúcia Padrão dos; Simões, Antonio Carlos (Saúde e Sociedade, 2012)
The study of the quality of life of individuals has become a prominent issue for contemporary society. However, research involving quality of life should consider that this is a complex issue that involves objective and subjective aspects, living conditions, lifestyles and multidimensional factors. There is a widespread idea in society that physical activity, exercise, sports and related activities can have a positive impact on improving the quality of life of the population. However, in several studies, this relationship is examined from the biological point of view, which considers only health indicators. Such practices are being studied in the area of Physical Education in various perspectives, such as biological, psychological, social, and cultural. Therefore, Physical Education should seek to produce knowledge that meets the scientific principles, and look for evidence that effectively clarifies the dynamics of this relationship. In this sense, methodological rigor, particularly the conceptual definition, is essential for a better understanding of the results and of which generalizations are actually likely to e proved. In addition, it is necessary to identify the possibilities and limitations of quantitative evaluations, qualitative evaluations and possible combinations.